Efek Interaksi Sosial Digital terhadap Impulsivitas Belanja Online pada Generasi Z - Latif, Ayi Abdul; Kartika Dwifa Siregar; M. Rafeli Iskandar; Ririn Nur Widyastuti; Mia Lasmi Wardiyah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The rapid growth of digital technology and social media has changed the way individuals interact and make decisions in shopping, especially among Generation Z who are very active in the online environment. This study aims to analyze the influence of digital social interactions on online shopping impulsivity in Generation Z. This study explores how exposure to digital peer influence, user-generated content, and social engagement through platforms such as Instagram, TikTok, and online forums drive unplanned shopping behavior. This study uses a quantitative approach with a survey of 30 Generation Z respondents aged 18–25 years who are active online shoppers and involved in digital social platforms. Data analysis was conducted using simple linear regression to test the relationship between digital social interactions and impulsive shopping tendencies. The results showed a significant positive relationship, where the higher the intensity of digital social interactions, the higher the level of impulsivity in online shopping. These findings indicate that digital social influences play an important role in shaping the consumption behavior of the younger generation. This study contributes to the development of literature in consumer psychology and digital behavior, as well as being the basis for formulating ethical digital marketing strategies and consumer education in the digital era.